Bimodulus bending model for bamboo poles. (30th November 2020) - Lorenzo, Rodolfo; Mimendi, Leonel; Li, Haitao; Yang, Dong
Highlights: Bimodulus model to determine the strain and stress distribution of bamboo poles in bending. Analytical model based on experimental testing of small clear bamboo samples. Model validation based on full-scale experimental four-point bending tests. Proposed model predicts the cross-sectional elastic strain and stress distributions. Abstract: The building industry is currently under pressure to transit from non-renewable materials with high embodied energy towards natural and sustainable options. Bamboo poles are some of the most promising renewable structural elements, but their formal utilisation in construction requires the development of appropriate analytical models and new design tools to address their challenging natural and organic nature. Considering the composite nature of bamboo poles and the properties of their high-strength sclerenchyma fibres and parenchyma matrix, this paper presents the formulation of an analytical bimodulus model to determine the cross-sectional strain and stress distribution in bamboo poles in bending. This model was validated through full-scale experimental four-point bending tests on Moso ( Phyllostachys pubescens ) bamboo poles suggesting a constant tensile elastic modulus of fibres for this species.